Blended Snowballing Discussion Technique and Collaborative Learning Pedagogy in EFL Speaking - Ranta Butarbutar; Seeni Mehraj Begam Binti V.K.S. Vyzul Karnine (GLENS: Global English Insights Journal, 2024)
The objective of this qualitative case study is to investigate BSD issues, solutions, and collaborative learning approaches in EFL courses. As part of a case study, researchers examined the design and gathered information through open-ended interviews, documents, digital recorders, forum group discussions (FGD), and pertinent literature. All the gathered data were examined through exploration. Accordingly, the FGD forum was used to its fullest potential during the data analysis process for cross-checking, validation, verification, and confirmation. Teachers used pre-teaching (planning), cooperation (observing, supporting, and consolidating), reflection, and evaluations to achieve their goals. In this way, teachers encounter issues such as (1) choosing topics based on what students already know, (2) lack of group cohesion, (3) distinction between group and individual assessment, (4) lack of constructive interdependence, (5) variety of learning styles, and (6) inactivity. More research will be required in the future, as the study only examined a limited sample of people. There are recommendations for future experimental language lab classes. Blended EFL classes typically require the construction of an EFL curriculum through collaboration and technology, based on spontaneous speech activities, to ensure students' preparation before and after their participation.